Current applications of da vinci SP surgical system in gynecologic surgery - Johnny Yi (Intelligent Surgery)
Single incision surgery is a form of minimally invasive surgery performed typically through a 2–3 ​cm incision in the umbilicus. Single incision laparoscopy has significant challenges and a long learning curve due to the difficulties in triangulation and the lack of articulating instrumentation. Single site robotics attempted to overcome this with advantages of 3-D visualization and some introduction to articulating instrumentation. In 2019, the single port robotic platform (SPORT) was introduced, which has significant advantages in single incision surgery. Applications in gynecologic surgery have been described for benign, reconstructive and malignant conditions. This technology shows promise in further minimizing surgical approach for gynecologic surgery, but further level 1 studies are needed to demonstrate its place compared to other existing technologies.